2005
DOI: 10.1097/01.mlg.0000161362.43320.b2
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Survival and Glial Reactions after Recurrent Laryngeal Nerve Resection in the Rat

Abstract: Neuronal death does not occur within 1 month postlesion as a result of resection of the RLN in the adult rat, and neuroprotective substances should therefore be of minor value after RLN injury. Glial reactions appear in a similar fashion as after other peripheral nerve lesions not causing neuronal loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(43 citation statements)
references
References 16 publications
1
42
0
Order By: Relevance
“…This phenomenon was not adjusted for, because our earlier results showed that a similar injury (RLN resection) in the same system causes no neuronal loss. 18 Analysis of PCA Muscle Sections. Muscle sections were analyzed using a Leica confocal system (TCS SP2) connected to a Leica DMIRE2 microscope with a 63ϫ/1.40 -0.60 objective.…”
Section: Quantification Of Retrogradely Traced Pca Neuronsmentioning
confidence: 99%
“…This phenomenon was not adjusted for, because our earlier results showed that a similar injury (RLN resection) in the same system causes no neuronal loss. 18 Analysis of PCA Muscle Sections. Muscle sections were analyzed using a Leica confocal system (TCS SP2) connected to a Leica DMIRE2 microscope with a 63ϫ/1.40 -0.60 objective.…”
Section: Quantification Of Retrogradely Traced Pca Neuronsmentioning
confidence: 99%
“…They may be summarized by cortical contact, neuronal survival, pace of regeneration, misguidance, and degree of muscle atrophy. After injury to the RLN, there have been speculations about misguidance into the adductor and abductor branches of the nerve causing the loss of functional restitution, hampered coordination, or synkinesis of the vocal cord 6 . There is also evidence of rapid occupation of motor end plates in the larynx muscles by autonomous fibers after RLN injury 7 .…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that the endogenous NPCs attempt to repair the lesioned NA. It is generally known that a retrograde axonal reaction can be caused by injury of a peripheral motor nerve [14]. Decreased motor neuron survival numbers, reactive microglia, astrocytes and macrophages were observed after the RLN avulsion injury in our previous report [12].…”
Section: Discussionmentioning
confidence: 66%